Knowledge Creation Process for Organizational Creativity and Performance in Nepalese Hospitality Industry - Maharjan, Pushpa (Nepalese Journal of Management Science and Research, 2023)
This paper analyses the relationships between the knowledge creation process and organizational creativity; organizational creativity and organizational performance in the hospitality industry such as hotel, travel and trekking agencies in Nepal. The study is based on primary data with 382 responses. The self-administered questionnaires were used to collect the perceptive opinions from the respondents. The study concludes that the key knowledge creation process such as socialization, externalization, combination and internalization do influence to the organizational creativity positively and organizational creativity influences to the organizational performance positively. Managers should promote socialization, externalization, combination, internalization and creativity for employees to get better organizational performance.